Efficacy and safety of adalimumab in Japanese patients with psoriatic arthritis and inadequate response to non-steroidal anti-inflammatory drugs (NSAIDs): A prospective, observational study. Issue 1 (2nd January 2020) - Morita, Akimichi; Okuyama, Ryuhei; Katoh, Norito; Tateishi, Chiharu; Masuda, Koji; Komori, Toshifumi; Ogawa, Eisaku; Makino, Takamitsu; Nishida, Emi; Nishimoto, Shohei; Muramoto, Kenzo; Tsuruta, Daisuke; et al.
Abstract: Objectives: To evaluate the efficacy and safety of adalimumab in psoriatic arthritis (PsA) patients in Japan. Methods: In this open-label, single-arm study conducted at six sites from October 2014 to June 2016 (UMIN000016543), PsA patients (≥20 years old) with inadequate response to nonsteroidal anti-inflammatory drugs received adalimumab subcutaneously (80 mg initially, then 40 mg every other week; 24 weeks total). Primary endpoint was American College of Rheumatology 20% improvement (ACR20) response rate at week 12. Results: Of 42 enrolled patients, 37 were treated (mean (SD) age, 56.2 (13.0) years; male, 27 (73.0%)). ACR20, ACR50, and ACR70 response rates were 40.5%, 24.3%, and 16.2% at week 12 and increased to 45.9%, 37.8%, and 21.6% at week 24, respectively. Psoriasis Area and Severity Index (PASI) 50 response rates were unchanged at weeks 12 and 24 (73%), but PASI75 and PASI90 increased from 40.5% and 21.6% to 59.5% and 40.5%, respectively. Other indices such as Physician's Global Assessment score, C-reactive protein-based disease activity score in 28 joints, Bath Ankylosing Spondylitis Disease Activity Index, and serum biomarker levels were significantly improved. No unexpected adverse events were reported. Conclusion: Similar to the global population, adalimumab was efficacious and well tolerated in Japanese treatment-experienced PsA patients.